Socio-demographic characteristics and risk factors for HIV transmission in female bar workers in sub-Saharan Africa: a systematic literature review - Dambach, Peter; Mahenge, Bathsheba; Mashasi, Irene; Muya, Aisa; Barnhart, Dale A.; Bärnighausen, Till; Spiegelman, Donna; Harling, Guy (BMC public health, 2020)
Although sex workers are considered a key population in the HIV epidemic in sub-Saharan Africa (SSA), less consideration has been given to female bar workers (FBW), whose primary occupation is not sex work but who often engage in transactional sex. Understanding FBWs’ risk profiles is central to designing targeted HIV prevention interventions for them. This systematic review describes the socio-demographic characteristics and risk factors for HIV transmission among FBWs in SSA.
Gesehen am 30.03.2021